2007
DOI: 10.1007/s00134-007-0718-8
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin therapy for arterial thrombosis in infants with congenital heart disease

Abstract: Objective: To investigate efficacy and safety of enoxaparin for catheter-related

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 25 publications
(27 reference statements)
2
31
0
2
Order By: Relevance
“…100,101,[103][104][105][106][107][108][109][110][111] One study reported oncedaily and bid enoxaparin targeted to a range of 0.5 to 0.8 units/mL measured 2 h after dose. 52 The relationship between the target therapeutic range and the clinical outcomes is unknown in neonates.…”
Section: 4-25 Cvad Prophylaxis In Neonatesmentioning
confidence: 99%
See 1 more Smart Citation
“…100,101,[103][104][105][106][107][108][109][110][111] One study reported oncedaily and bid enoxaparin targeted to a range of 0.5 to 0.8 units/mL measured 2 h after dose. 52 The relationship between the target therapeutic range and the clinical outcomes is unknown in neonates.…”
Section: 4-25 Cvad Prophylaxis In Neonatesmentioning
confidence: 99%
“…238 A recent report suggested that LMWH may be a safe alternative in this situation, although the possible need for thrombolysis or surgery makes LMWH a less attractive option. 103 If , 4 h have passed since the CC-related UFH bolus was given, then UFH may be commenced as a continuous infusion without a bolus. In acute limb-threatening thrombosis, indirect evidence from adults supports the use of thrombolytic or surgical interventions.…”
Section: 9-210 Therapy For Femoral Artery Thrombosis In Neonates Amentioning
confidence: 99%
“…A previous study of 31 children reported that a mean dose of 0AE83 mg/kg twice-daily for neonates and 0AE62 mg/kg twice-daily for children older than 2 months was required to achieve target range (Dix et al, 2000). In addition, a recent study reported that increasing the starting dose of enoxaparin may result in a more rapid achievement of the therapeutic range and fewer dose adjustments (Bauman et al 2009).The majority of studies of enoxaparin in children have reported a higher treatment dose requirement to achieve antiXa target range (0AE5-1AE0 i/u/ml), particularly in neonates, as compared to adults (Dix et al, 2000;McCusker et al, 2003;Streif et al, 2003;Ho et al, 2004;Manco-Johnson, 2006, Bontadelli et al, 2007Malowany et al, 2007). A number of studies further reported an increased dose requirement in …”
mentioning
confidence: 99%
“…Enoxaparin has been demonstrated to be effective in the treatment of catheter-associated arterial thrombosis in pediatric patients with congenital heart disease (30,31). In addition, Enoxaparin has been associated with a reduction in the risk of thrombotic complications when compared with no therapy in one study of pediatric patients with single ventricle cardiac lesions after initial palliation (stage I) and after superior cavopulmonary connection (stage II) (32).…”
Section: Moamentioning
confidence: 98%